Urbanissime Strada Jacopo Strada and cultural patronage at the imperial court - Jansen, Dirk Jacob 1953- (2015)
This book gives a survey of the career of the Renaissance antiquary Jacopo Strada (Mantua 1515- Vienna 1588). Aspects discussed include his background, education and artistic training; his early activities in Germany; his trips to Lyon and Rome and the origins of his huge collection of visual documentation of Antiquity and of canonical modern works of art; and his appointment as architect and antiquary to Emperors Ferdinand I and Maximilian II. The second part discusses Strada’s activities as architect and his share in projects of his imperial patrons in Vienna, the Munich Antiquarium, his own house and for private patrons. The third part discusses Strada’s role in purveying antiques and works of art for his patrons, contents and function of his own collection or "Musaeum", and his ambition to set up as an international publisher. The conclusion first defines Strada’s self-image as an antiquary; applying some of the terms of Everett Rogers’ theory of the diffusion of innovations, it then demonstrates how, and to what extent, Strada’s activities and the presence of his "Musaeum" in Vienna contributed to the acceptance of the ideas and the artistic idiom of the Italian High Renaissance to the north of the Alps.